Evaluation of 3M™ Molecular Detection Assay (MDA) Listeria monocytogenes for the Detection of Listeria monocytogenes in Selected Foods and Environmental Surfaces: Collaborative Study, First Action 2014.07. (27th November 2019) - Bird, Patrick; Flannery, Jonathan; Crowley, Erin; Agin, James; Goins, David; Monteroso, Lisa; Benesh, DeAnn; ,
Abstract: The 3M™ Molecular Detection Assay (MDA) Listeria monocytogenes combines isothermal amplification and bioluminescence to detect Listeria monocytogenes with high specificity and efficiency in select foods and environmental samples. The 3M MDA Listeria monocytogenes method was evaluated using an unpaired study design in a multilaboratory collaborative study to the U.S. Department of Agriculture, Food Safety and Inspection Service Microbiology Laboratory Guidebook 8.09 (2011) Isolation and Identification of Listeria monocytogenes from Red Meat, Poultry, and Egg Products and Environmental Samples for deli turkey, and the AOAC Official Method of Analysis SM 993.12 Listeria monocytogenes in Milk and Dairy Products for full-fat (4% milk fat) cottage cheese following the current AOAC guidelines. A total of 16 laboratories located in the continental United States and Canada participated in this collaborative study. For deli turkey, 125 g test portions were evaluated using heat-stressed cells by each method. For full-fat cottage cheese, 25 g test portions were evaluated using nonheat-stressed cells. Each matrix had three inoculation levels: an uninoculated control level (0 CFU/test portion), and two levels artificially contaminated with L. monocytogenes, a low inoculum level (0.2–2 CFU/test portion) and a high inoculum level (2–5 CFU/test portion). In total, 1584 unpaired replicate samples were analyzed. Statistical analysis was conducted according to the probability of detection (POD) model. Results obtained for the low inoculum level full-fat cottage cheese test portions produced a difference in cross-laboratory POD (dLPOD) value of –0.08 with a 95% confidence interval (CI) of (–0.20, 0.05). For the low-level deli turkey test portions, a dLPOD value of –0.02 with a 95% CI of (–0.14, 0.11) was obtained.